2017
DOI: 10.5430/ijelt.v4n2p39
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Punctuation Errors Made by Secondary School Students in English Language Comprehension in Ogun State, Nigeria

Abstract: This study assessed the errors in English comprehension by Senior Secondary School Students. Errors in English punctuation in this study were categorized as mechanical errors in comprehension with particular emphasis on punctuation marks and spelling. This study adopted a descriptive research design of ex-post-facto type. The target groups for the study were Ogun State Secondary Schools in Nigeria. The samples were drawn from four (4) geo-political zones in Ogun State of Nigeria (Ijebu, Remo, Yewa and Egba). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Turkish EFL students according to Elkılıç et al (2009) should be taught punctuation explicitly and compared to Turkish punctuation conventions. Assessing punctuation errors made by secondary school students in Ogun State, Nigeria was done by Adekola & Lawal (2017) who found out that these errors are significantly related to the students' overall performance at school and suggested paying a greater attention to reading and writing comprehension. The third-year students at the secondary schools in Sudan have been tested on the correct punctuation use and the research results showed various errors, including those in the commas usage.…”
Section: Introductionmentioning
confidence: 99%
“…Turkish EFL students according to Elkılıç et al (2009) should be taught punctuation explicitly and compared to Turkish punctuation conventions. Assessing punctuation errors made by secondary school students in Ogun State, Nigeria was done by Adekola & Lawal (2017) who found out that these errors are significantly related to the students' overall performance at school and suggested paying a greater attention to reading and writing comprehension. The third-year students at the secondary schools in Sudan have been tested on the correct punctuation use and the research results showed various errors, including those in the commas usage.…”
Section: Introductionmentioning
confidence: 99%